Gold nanorod assemblies on polymer brushes for protein sensing - Mohamed Muhaimin Mohamed Mokh'ee (2014)
With advancement in nanotechnology in the biosensors field, great interest was generated in nanomaterials used due to their high sensitivity in chemical and biological sensing. Amongst all the nanomaterials, gold nanoparticles received the highest interest. Its ability to exhibit singular optical responses, due to localized surface plasmon resonance, and low toxicity in the biological environment makes it useful to use as a colorimetric probe for biomedical purposes. This project was conducted to develop a robust polymer-nanoparticle composite, gold in a poly (oligo (ethylene glycol) methacrylate)-based matrix. Since the polymer brush is grown on clear glass coverslips, a novel solid-phase colorimetric sensor can be fabricated as a result from this project. Studies were done on how certain factors affect the growth of the polymer brush, gold nanoparticle immobilization by the polymer brush and protein detection. Each test series conducted was conducted independent of the other. Only 1 variable was changed at each time and the rest were kept constant to isolate each factor and study it. The results were consistent and provide conclusive evidence on ways to fine tune the polymer growth and nanoparticle immobilization to obtain optimal loading capacity and loading density. Protein detection was done in 2 different mediums; (1) in thrombin binding buffer and (2) human serum. Results indicated that protein could be detected in each case; however, the sensitivity can be improved further.